Developing ETeMS teachers' speaking skills through communicative approach / Siti Hajjar Sheikh Mohd Fazil - Sheikh Mohd Fazil, Siti Hajjar (2010)
This study aimed to develop ETeMS teachers' speaking skill through Communicative Approach activities. It investigated and identified the problems that the teachers face when they taught Mathematics and Science in English. This study was designed to implement the selected Communicative Approach activities that can develop the teachers' speaking skills, improve their confidence and motivate them to conduct their lessons in English. It was a descriptive study that incorporated quantitative and qualitative data through the use of questionnaire and structured interviews. This study involved twelve primary school teachers who taught Mathematics and Science in English. Pre and post oral test was conducted at the beginning and the end of the study to indicate if the teachers' speaking skills were improved. Descriptive statistics namely mean and standard deviation were used to analyze the responses in the questionnaire. Paired sample t-test is used to analyze the pre and post oral test. Findings from the study indicated that the teachers' speaking skills did improve throughout the study and they gained confidence and motivation to teach Mathematics and Science in English. This study could implicate on how our education system would benefit from communicative activities in the classroom in promoting more Malaysian to speak fluent and accurate English.